Transplante hepático por hepatite D e análise comparativa com transplantados por hepatite B - Lima, Daniel Souza (2012)
The Amazon region is one of the main endemic areas of hepatitis D in the World and the only related to the presence of genotype 3 of delta virus. The objective of this study was to analyze the results of liver transplantation for cirrhosis caused by hepatitis D and correlate with the transplant by monoinfection of hepatitis B. 29 patients were evaluated with hepatitis D and 40 patients with hepatitis B, they were submitted a liver transplantation in the Walter Cantidio University Hospital of the Federal University of Ceara. The group of patients with hepatitis D were younger (mean 33.9 vs 52.9 years, p < 0,001), predominantly male and all from the Brazilian Amazon region. There were no differences in the values of severity criteria, MELD and Child, between groups. The occurrence of hepatocellular carcinoma (HCC) was predominant in patients with hepatitis B (frequency 36.8% vs. 17.2%, p = 0,05), likewise higher mortality (frequency 25% vs 3.4%, p = 0,019). Patients with hepatitis D showed more pronounced thrombocytopenia in pre-transplant (mean 66.428,57 vs 102.037,50 µL, p = 0,02) and in the immediate postoperative period (mean 54.242,86 vs 94.063,89 µL, p = 0,04). The recovery of liver injury as measured by the values of AST, ALT, and BT, measured 3 months after transplantation showed no difference between groups. The survival analyzed by Kaplan-Meier survival curves, showed a period of four years, the result of 95% in patients with hepatitis D and 75% in patients with monoinfection of hepatitis B. Patients with hepatitis D have excellent results after liver transplantation and lower incidence of HCC development.